2021
DOI: 10.1186/s41021-021-00208-z
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR A1298C gene polymorphism on stroke risk: an updated meta-analysis

Abstract: Background Previous studies have shown the effect of MTHFR A1298C gene polymorphism on stroke risk. But the results of published studies remained inconclusive and controversial. So we conducted a meta-analysis to accurately estimate the potential association between MTHFR A1298C gene polymorphism and stroke susceptibility. Methods A systematic literature search on Embase, Pubmed, Web of Science, Cochrane Library, China National Knowledge Infrastruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
5
1
Order By: Relevance
“…The association of MTHFR A1298C polymorphism with brin clot properties has been reported before 26 . Although MTHFR A1298C polymorphism has been reported to be associated with stroke 27 , in the present study there was no association either in bivariate or logistic regression analyses (Table 5). However, in the present study we found that MTHFR C677T polymorphism was associated with stroke (Table 5), consistent with earlier studies 16 .…”
Section: Discussioncontrasting
confidence: 78%
“…The association of MTHFR A1298C polymorphism with brin clot properties has been reported before 26 . Although MTHFR A1298C polymorphism has been reported to be associated with stroke 27 , in the present study there was no association either in bivariate or logistic regression analyses (Table 5). However, in the present study we found that MTHFR C677T polymorphism was associated with stroke (Table 5), consistent with earlier studies 16 .…”
Section: Discussioncontrasting
confidence: 78%
“…For ischemic stroke, very recent meta-analysis estimated the potential relationship between MTHFR A1298 gene polymorphism and ischemic stroke susceptibility; this review involved 5725 cases versus 8655 controls in 40 studies, these results indicated the polymorphism in MTHFR A1298C gene has significant association with increase susceptibility of ischemic stroke under the C allelic genetic model. Additionally, in ethnic subgroup analysis MTHFR A1298C gene polymorphism was correlated with stroke risk of Asian populations, whereas there was no significant correlation among MTHFR A1298C gene polymorphism and increase risk of ischemic stroke in Caucasian and African populations (35).…”
Section: Mthfr A1298cmentioning
confidence: 75%
“…Association of rs1801131 with tHcy and stroke susceptibility is inconsistent. In a meta-analysis including 5725 cases and 8655 controls, evidence supported a correlation between MTHFR rs1801131 and stroke susceptibility (Dong et al, 2021). However, few studies have focused on rs1801131 and SVD; indeed, only one study has shown an association between mutations at A1298C with decreased tHcy levels and reduced brain parenchymal fractions (Cao et al, 2021).…”
Section: Discussionmentioning
confidence: 99%